ANALISIS MINAT PETERNAK DALAM MENGEMBANGKAN USAHA PETERNAKAN SAPI POTONG DI KECAMATAN WAELATA KABUPATEN BURU - Muh. Alfarid Souwakil; George S. J. Tomatala; Michel J. Matatula (MARSEGU : Jurnal Sains dan Teknologi, 2026)
This study was designed to evaluate the level of interest among farmers in developing beef cattle businesses while identifying the factors that influence it in Waelata District, Buru Regency. A survey method was employed, involving 30 beef cattle farmers as the research sample. Data were gathered through three approaches, namely direct observation, in-depth interviews, and questionnaire distribution. Farmer interest (Y) was positioned as the dependent variable, while economic conditions (X₁), social conditions (X₂), and environmental conditions (X₃) served as independent variables. The analytical techniques applied included descriptive statistics and multiple linear regression. The findings reveal that farmers' interest in developing beef cattle businesses falls into the very high category, with a mean score of 24.63. The regression equation obtained is: Y = 17.689 + 0.351X₁ + 0.227X₂ − 0.288X₃. Simultaneous testing confirmed that all three factors collectively exert a significant influence on farmer interest, as indicated by an F-value of 24.757. In partial testing, economic and social factors demonstrated a significant positive effect, whereas the environmental factor showed a significant negative effect. Among the three, the economic factor emerged as the most dominant variable. The coefficient of determination (R²) of 0.741 indicates that 74.1% of the variation in farmer interest can be explained by these variables, while the remaining 25.9% is attributed to other factors outside the scope of this study.